Metabolic Characterization of Hyoscyamus niger Ornithine Decarboxylase - Zhao, Tengfei; Wang, Changjian; Bai, Feng; Li, Siqi; Yang, Chunxian; Zhang, Fangyuan; Bai, Ge; Chen, Min; Lan, Xiaozhong; Liao, Zhihua (Frontiers in Plant Science, 2019)
Ornithine decarboxylase (ODC) catalyzes ornithine decarboxylation to yield putrescine, a key precursor of polyamines and tropane alkaloids (TAs). Here, to investigate in depth the role of ODC in polyamine/TA biosynthesis and to provide a candidate gene for engineering polyamine/TA production, the ODC gene (HnODC) was characterized from Hyoscyamus niger, a TA-producing plant. Our phylogenetic analysis revealed that HnODC was clustered with ODC enzymes of plants. Experimental work showed HnODC highly expressed in H. niger roots and induced by methyl jasmonate (MeJA). In the MeJA treatment, the production of both putrescine and N-methylputrescine were markedly promoted in roots, while contents of putrescine, spermidine, and spermine were all significantly increased in leaves. By contrast, MeJA did not significantly change the production of either hyoscyamine or scopolamine in H. niger plants. Building on these results, the 50-kDa His-tagged HnODC proteins were purified for enzymatic assays. When ornithine was fed to HnODC, the putrescine product was detected by HPLC, indicating HnODC catalyzed ornithine to form putrescine. Finally, we also investigated the enzymatic kinetics of HnODC. Its Km, Vmax, and Kcat values for ornithine were respectively 2.62±0.11 mM, 1.87±0.023 nmol min-1 μg-1 and 1.57±0.015 s-1, at pH 8.0 and at 30 ˚C. The HnODC enzyme displays a much higher catalytic efficiency than most reported plant ornithine decarboxylases, suggesting it may be an ideal candidate gene for engineering polyamine/TA biosynthesis.